Exposure to N,N-diethyl-m-toluamide and cardiovascular diseases in adults - Yan, Shiwei; Wang, Jianing; Xu, Jiaxu; Jiang, Wenbo; Xiong, Menglin; Cao, Ziteng; Wang, Yu; Wang, Ziqi; Zhang, Tongfang; Wang, Zheng; Sun, Changhao; Hou, Shaoying; et al. (Frontiers in Public Health, 2022)
Although growing evidence suggests that N,N-diethyl-m-toluamide (DEET) has adverse effects on public health, the relationship of DEET with cardiovascular disease (CVD) is still largely unknown. The purpose of this study was therefore to evaluate the association between DEET exposure and total and specific CVD among US adults. In this cross-sectional study, a total of 5972 participants were selected from National Health and Nutrition Examination Survey (NHANES) 2007-2014. CVD was defined by a combination of congestive heart failure, coronary heart disease (CHD), angina, heart attack, or stroke. Logistic regression models were used to evaluate the association between DEET metabolites and the risks of total and specific CVD. Compared to the lowest quartile, DCBA in the highest quartile was associated with the increased risks of CVD (OR: 1.32, 95% CI: 1.03-1.68, P for trend= 0.025) and CHD (OR: 1.57, 95% CI: 1.10-2.25, P for trend= 0.017), after adjustment for potential covariates. Nevertheless, exposure to DCBA was not significantly associated with heart attack, congestive heart failure, angina, and stroke. Further studies are required to confirm these findings and identify the underlying mechanisms.